The awesome human project : break free from daily burnout, struggle less, and thrive more in work and life - Kogan, Nataly (Sounds True, 2022)
"The Awesome Human Project is an accessible, super-practical book that teaches the emotional fitness skills so many of us need to struggle less, have more energy, and experience more meaning and joy in life and at work"--